2018
DOI: 10.1002/anie.201812094
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Single‐Crystal‐to‐Single‐Crystal Evolution of Two Cross‐Laminated Polymers

Abstract: Twocases of spontaneous evolution of monomers to linear polymers having novel cross-laminated topology are reported. We synthesized two peptide monomers N 3 -Gly-Gly-NH-CH 2 -CCH and N 3 -Gly-Gly-Gly-CH 2 -CCH and solved their crystal structures by single-crystal X-raydiffraction. They adopt H-bonded crisscrossed layered packing in their crystals such that:( a) the monomers are aligned head-to-tail in 1Dchain-like arrays and parallel arrangement of such arrays forms al ayer;( b) the proximally placed azide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Overall, considering the complexity of further decomposing single contributions to the interaction energy into specific parts of the molecular systems, the unbiased azide–X interaction is estimated to be 1.5 to 3.0 kcal mol −1 . We are convinced that these stabilizing interactions are of importance, not only for the arrangement of azide moieties in supramolecular assemblies and crystal engineering (e.g., click chemistry in the solid state), [81–85] but are also the basis for conformational bias in azido‐functionalized nucleic acids, peptides, proteins, and carbohydrates. Future investigations will reveal whether azido‐based interactions have a similar potential to facilitate catalysis, as has been extensively and successfully explored for halogen and chalcogen bonding.…”
Section: Resultsmentioning
confidence: 96%
“…Overall, considering the complexity of further decomposing single contributions to the interaction energy into specific parts of the molecular systems, the unbiased azide–X interaction is estimated to be 1.5 to 3.0 kcal mol −1 . We are convinced that these stabilizing interactions are of importance, not only for the arrangement of azide moieties in supramolecular assemblies and crystal engineering (e.g., click chemistry in the solid state), [81–85] but are also the basis for conformational bias in azido‐functionalized nucleic acids, peptides, proteins, and carbohydrates. Future investigations will reveal whether azido‐based interactions have a similar potential to facilitate catalysis, as has been extensively and successfully explored for halogen and chalcogen bonding.…”
Section: Resultsmentioning
confidence: 96%
“…In form II , a molecule of chloroform occupies the position B (Figure b) and this prevents the attainment of proximal arrangement of azide and alkyne groups for the TAAC reaction to proceed. We have previously observed that many crystals having azide and alkyne groups at proximity and in reactive orientation can undergo spontaneous TAAC reaction even at room temperature . In this context, the temporary prevention of attaining the reactive arrangement by the guest (chloroform) molecules is beneficial for long‐time storage of the crystals in the unreactive state.…”
Section: Resultsmentioning
confidence: 99%
“…14d and e ). 63 Both the monomers 47 and 48 evolve spontaneously to the respective polymers via TAAC polymerization ( Fig. 14f ) in a SCSC fashion.…”
Section: Novel Topologiesmentioning
confidence: 99%